A PROSPECTIVE OBSERVATIONAL STUDY TO COMPARE THE CLINICAL OUTCOME OF PREGABALIN AND AMITRIPTYLINE IN NEUROPATHIC PAIN - Dr. Neethu Soman; Dr. Kala Kesavan P. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BackgroundNeuropathic pain has a significant negative impact on the patients’ quality of life. Antidepressants like Amitriptyline and newer anticonvulsants such as Pregabalin have been proven beneficial in patients with peripheral neuropathic pain. Studies comparing the real-world effectiveness and safety of drugs for neuropathic pain are scarce.Aims and objectivesThe aim of the study was to compare the efficacy and safety of Pregabalin and Amitriptyline in relieving neuropathic pain.MethodsAfter ethics committee approval and informed consent, 200 outpatients (100 each) prescribed any one of the drugs were consecutively recruited in a prospective observational study. Drug effectiveness was assessed by comparing difference in visual analogue scale (VAS) score from baseline, obtained from pain diary. The quality of pain was assessed by using the Short Form Mc Gill Pain Questionnaire (SF-MPQ). Safety was assessed by comparing frequency of adverse drug reactions (ADRs).ResultsThe difference in mean VAS score at 12 weeks showed that Amitriptyline group had a greater reduction in pain compared to Pregabalin. Patients in Amitriptyline group also had a greater reduction in Mc Gill sensory, affective and total scores after 12 weeks. Adverse reactions like sedation, dizziness, lack of concentration, fatigue, dry mouth occurred in both groups, but Amitriptyline group had higher incidence of sedation, dizziness and dry mouth.ConclusionAmitriptyline was more effective in relieving neuropathic pain compared to Pregabalin. Higher incidence of sedation, dry mouth and dizziness was observed in Amitriptyline treated group compared to Pregabalin.